IDDF2019-ABS-0278 Fusobacterium nucleatum promotes malignant progression of colorectal cancer by activating NF-kB/NCOA7-AS1/IKK positive feedback loop. (June 2019) - Yan, Changsheng; Zhang, Xiang
Abstract : Background: As Fusobacterium nucleatum has been demonstrated to play an important role in the progression of colorectal cancer. To elucidate the potential mechanism of Fusobacterium nucleatum in the malignant progression of colorectal cancer is of big importance. Methods: The dataset in the colorectal cancer group was analyzed by edger function and limma function. QRT-PCR was conducted to detect gene and bacterial expressive abundances. Regulatory effects of Fusobacterium nucleatum on cellular behaviors of colorectal cancers were evaluated through CCK-8, wound healing assay and flow cytometry. The binding relationship and interaction between NF-kB and NCOA7-AS1 were verified through dual-luciferase reporter gene assay, ChIP and functional experiments. Moreover, proteins that bind to NCOA7-AS1 were determined by RNA-Pull down, mass spectrometry and RIP. Results: LncRNA NCOA7-AS1 is upregulated in colorectal cancer infected with Fusobacterium nucleatum . Correlation analysis showed that the abundance of Fusobacterium nucleatum was positively correlated with NCOA7-AS1 level. Fusobacterium nucleatum could accelerate the malignant phenotypes of colorectal cancer, which were partially reversed by the silence of NCOA7-AS1. NF-kB was verified to bind to the NCOA7-AS1 promoter region to upregulate NCOA7-AS1. Furthermore, NCOA7-AS1 was identified to bind to IKK and developed positive feedback to activate the NF-KB pathway, thereby promoting the progression of colorectal cancer. Conclusions: Fusobacterium nucleatum activates the positive feedback loop NF-kB/NCOA7-AS1/IKK, thereby accelerating the malignant progression of colorectal cancer.